Letter to the Editor : Sylvatic Dengue Viruses Share the Pathogenic Potential of Urban/Endemic Dengue Viruses - Vasilakis, Nikos; Cardosa, Mary Jane; Sall, Amadou A.; Diallo, Mawlouth; Holmes, Edward C.; Hanley, Kathryn A.; Weaver, Scott C. (American Society for Microbiology, 2010)
Dengue virus (DENV) exists in both sylvatic and urban/endemic ecotypes (15), and the potential for emergence of sylvatic strains has become a focus of research. Recently Mota and Rico-Hesse (10) attempted to evaluate the pathogenic potential of viruses belonging to different genetic subgroups of DENV serotype 2 (DENV-2). Based on the viremia levels and erythema index profiles of one sylvatic genotype and three (Asian, American, and Indian) urban/endemic genotypes evaluated using the NOD-scid IL2rγnull humanized mouse model, the authors concluded that sylvatic DENV-2 viruses possess a reduced pathogenic potential compared to strains belonging to urban/endemic DENV-2 genotypes. However, these conclusions ignore both patterns in their own data and a wealth of published ex vivo, in vivo, and epidemiological evidence collected over the past 40 years.